Architecture of Iberian canopy tree species in relation to wood density, shade tolerance and climate - Poorter, Lourens; Lianes, Elena; Moreno-de las Heras, Mariano; Zavala, Miguel A. (Plant Ecology, 2012)
Tree architecture has important consequences for tree performance as it determines resource capture, mechanical stability and dominance over competitors. We analyzed architectural relationships between stem and crown dimensions for 13 dominant Iberian canopy tree species belonging to the Pinaceae (six Pinus species) and Fagaceae (six Quercus species and Fagus sylvatica) and related these architectural traits to wood density, shade tolerance and climatic factors. Fagaceae had, compared with Pinaceae, denser wood, saplings with wider crowns and adults with larger maximal crown size but smaller maximal height. In combination, these traits enhance light acquisition and persistence in shaded environments; thus, contributing to their shade tolerance. Pinaceae species, in contrast, had low-density wood, allocate more resources to the formation of the central trunk rather than to branches and attained taller maximal heights, allowing them to grow rapidly in height and compete for light following disturbances; thus, contributing to their high light requirements. Wood density had a strong relationship with tree architecture, with dense-wooded species having smaller maximum height and wider crowns, probably because of cheaper expansion costs for producing biomechanically stable branches. Species from arid environments had shorter stems and shallower crowns for a given stem diameter, probably to reduce hydraulic path length and assure water transport. Wood density is an important correlate of variation in tree architecture between species and the two dominant families, with potentially large implications for their resource foraging strategies and successional dynamics.
Keywords: Architecture; Crown traits; Drought; shade tolerance; Tree height; Wood density